Development Of Power Management Circuitry For Battery Less Body Patch - Abdul Halim, Zulkifli (Universiti Sains Malaysia, 2018)
When talking about wireless connection, the first thing come cross our mind is the wireless internet connection. Wireless connection is a trending thing, everything is wireless. This project was inspired by the wireless connection. The research is focusing on the development of battery less power management for body patch application in stress and temperature monitoring for human body. The concept of the circuit is same as transformers concept, the mutual inductance or inductive coupling, where the primary coil transfers the energy to the secondary coil. In this project the smart phone supported with NFC technology will transfer the energy to the antenna. In order to make a connection between smart phone and the circuit, frequency of both devices must be the same with the 13.56MHz and the inductor will generate curtain amount of voltage to supply to the circuit components. The project will involve inductor design as energy harvesting, then integrate with Texas power management IC.